Pursuing Diversity: The Context, Practices, and Diversity Outcomes of Intentionally Diverse Charter Schools. Issue 12 (December 2022) - Seifert, Sophia; Porter, Lorna; Cordes, Sarah A.; Wohlstetter, Priscilla
Background: In the United States, students' experiences are shaped by racioethnic, socioeconomic, and linguistic segregation. School choice, and especially charter schools, generally exacerbate existing levels of school segregation. Counter to this trend, hundreds of intentionally diverse charter schools (IDCS), with a mission to promote school diversity, have opened across the country. Purpose: This study aims to clarify how IDCS operationalize their mission to serve diverse populations. To do so, we examine contextual factors that influence diversification efforts, the strategies that IDCS use to pursue diverse enrollments, and whether sample IDCS are more diverse than comparison schools. Research Design: This study uses a convergent mixed-methods design, in which qualitative and quantitative data were independently collected and analyzed, then merged for final analysis. The qualitative phase included thematic analyses of 101 interviews and 40 focus groups with IDCS staff and leaders to identify key contextual factors and practices that shape diversification efforts. For quantitative analyses, we used student and school-level administrative data from sample and comparison schools in New York, Colorado, and California. We explored researcher-created diversity outcomes for sample and comparison schools, including a racioethnic diversity index representing the probability that any two students chosen at random will be of a different race/ethnicity, and locally created diversity goals of having 40%–50% of enrolled students qualify for free/reduced price lunch (FRL) and no racial majority group among enrolled students. Conclusions/Recommendations: We found that local context, including race-neutral state policies and local housing patterns, created barriers to recruiting and enrolling diverse students. To overcome these barriers, IDCS staff developed data-driven recruitment and enrollment practices that were differentiated by the target group. Practices focused on increasing awareness of the school, building trust, and investing parents in the schools' diversity mission. Enrollment data show that sample IDCS are more diverse than a set of comparison schools, with mixed results when analyzing diversity outcomes with locally defined goals. We conclude that, despite contextual barriers, choice schools have considerable agency in fostering school diversity.